Epoxy resin flame retardant based on three-dimensional core-shell structure nanoparticles as well as preparation method and application of epoxy resin flame retardant

By modifying epoxy resin with SiO2@PDA-HCCP three-dimensional core-shell nanoparticles, the problems of flammability and poor dispersibility of traditional flame retardants were solved, achieving a balance between high flame retardancy and mechanical properties with low addition amount.

CN120944193APending Publication Date: 2025-11-14SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511071005.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-31
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing epoxy resins are flammable, and traditional flame retardants require large amounts and have poor dispersibility, leading to fire hazards and reduced mechanical properties.

Method used

The SiO2@PDA-HCCP three-dimensional core-shell structure nanoparticles are used. By coating the surface of SiO2 nanospheres with polydopamine and hexachlorocyclotriphosphazene, a three-dimensional core-shell structure is constructed to achieve uniform dispersion and efficient flame retardancy of nanoparticles in epoxy resin.

Benefits of technology

It significantly improves the flame retardant and mechanical properties of epoxy resin at low addition levels, reduces the peak heat release rate, maintains the mechanical properties of the material, and achieves a V-1 flame retardant rating and a high LOI value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120944193A_ABST
    Figure CN120944193A_ABST
Patent Text Reader

Abstract

The invention discloses an epoxy resin flame retardant based on three-dimensional core-shell structure nanoparticles as well as a preparation method and application of the epoxy resin flame retardant. According to the flame retardant, nano SiO2 serves as a core, and the surface of the core is sequentially coated with PDA and HCC to form an organic-inorganic hybrid shell layer (SiO2 (at) PDA-HCCP). Dopamine is oxidized and self-polymerized under an alkaline condition to form a PDA coating, and coating is realized through interaction of rich catechol / amine groups and strong hydrogen bonds on the surfaces of the SiO2 nanospheres; afterwards, the high reaction activity of PDA is utilized, the amido of PDA and the active chlorine group of HCCP are subjected to a substitution reaction, HCCP rich in phosphorus and nitrogen is grafted to a PDA layer, and a three-dimensional core-shell structure is constructed. The obtained SiO2 (at) PDA-HCCP nanoparticles have good dispersibility in an epoxy resin matrix. When the flame retardant is applied to epoxy resin, the thermal stability and flame retardance of a composite material can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of epoxy resin flame retardants, specifically relating to an epoxy resin flame retardant based on SiO2@PDA-HCCP three-dimensional core-shell structure nanoparticles, its preparation method, and its application. Background Technology

[0002] Since the beginning of the 21st century, epoxy resin (EP), as a high-performance thermosetting material, has been widely used in aerospace, electronic packaging, and composite materials fields due to its excellent three-dimensional network structure, outstanding mechanical strength, chemical corrosion resistance, and low curing shrinkage. However, the high hydrocarbon content in epoxy resin molecules makes it inherently flammable, rapidly releasing high heat, dense smoke, and toxic gases (such as carbon monoxide) upon contact with fire, posing a significant fire hazard. Statistics show that fires caused by polymer materials result in huge economic losses and casualties annually, highlighting the necessity of flame-retardant modification.

[0003] The current mainstream method for improving the flame retardancy of epoxy resins is to add flame retardants. Commercial flame retardants mainly include halogenated (bromine / chlorine compounds), phosphorus-based organic compounds, and nitrogen-based additives. However, halogenated flame retardants release highly toxic fumes when burning, violating environmental protection trends; while phosphorus / nitrogen-based flame retardants require high addition levels (usually >20wt%) to be effective, which not only increases costs but also causes agglomeration due to poor dispersibility, severely damaging the mechanical properties of the material. These drawbacks greatly limit the application of epoxy resins in fire-resistant applications.

[0004] Nanoparticle flame retardants (such as silica, layered double hydroxides, and graphene) are considered potential solutions due to their large specific surface area and strong interfacial effects. However, unmodified nanofillers tend to aggregate in epoxy groups, leading to uneven dispersion, and high addition levels can actually weaken flame retardancy and mechanical properties. Research indicates that the organic functionalization of nanofillers is key to overcoming this bottleneck, requiring surface modification to improve dispersibility, interfacial compatibility, and synergistic flame retardant effects.

[0005] Hexachlorocyclotriphosphazene (HCCP), as a phosphorus- and nitrogen-rich flame retardant unit, has active chlorine groups that can react with hydroxyl / amino compounds to form cross-linked structures; polydopamine (PDA) combines the high adhesion of catechol / amine groups and free radical scavenging ability with the functions of surface modification carrier and intrinsic flame retardant.

[0006] Therefore, there is an urgent need to develop a novel flame retardant strategy that integrates the stability of inorganic nanocores (such as SiO2), the interface enhancement effect of PDA, and the gas / solid phase flame retardant function of HCCP through scalable three-dimensional core-shell structured nanoparticles, to achieve a balance between the flame retardancy and mechanical properties of epoxy resin at low addition levels. Summary of the Invention

[0007] The technical problem to be solved by the present invention is to provide an epoxy resin flame retardant based on SiO2@PDA-HCCP three-dimensional core-shell structure nanoparticles, which has good compatibility with epoxy resin and excellent flame retardant effect in application, in order to overcome the shortcomings of the prior art.

[0008] The technical solution adopted by the present invention to solve the above-mentioned problems is as follows:

[0009] A method for preparing SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles includes the following steps:

[0010] (1) Synthesis of SiO2 nanospheres: A solution A was prepared by mixing ammonia, water and anhydrous ethanol; a solution B was prepared by mixing tetraethyl orthosilicate (TEOS) and anhydrous ethanol; solution B was quickly added to solution A and stirred at 25-35℃ for 1-3 hours. After the reaction was completed, the suspension was centrifuged at 8000-9000 rpm for 3-5 minutes, the precipitate was washed with anhydrous ethanol and dried at 80-110℃ for 10-14 hours to obtain SiO2 nanospheres.

[0011] (2) Preparation of SiO2@PDA: The SiO2 nanospheres obtained in step (1) were dispersed in Tris-HCl buffer solution (concentration 5-15mM), dopamine hydrochloride was added, and the mixture was stirred at room temperature (20-25℃) for 20-28 hours. After the reaction was completed, the mixture was centrifuged and washed three times with deionized water to obtain SiO2@PDA powder.

[0012] (3) Preparation of SiO2@PDA-HCCP: SiO2@PDA powder, hexachlorocyclotriphosphazene (HCCP) and triethylamine (TEA) were added to tetrahydrofuran (THF) and stirred at 45-55℃ for 20-28 hours. After the reaction was completed, the mixture was centrifuged, washed three times with THF, and dried to obtain SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles.

[0013] Preferably, in step (2), the mass ratio of SiO2 nanospheres to dopamine hydrochloride is 1:(0.3-0.5).

[0014] Preferably, in step (3), the mass ratio of SiO2@PDA powder to hexachlorocyclotriphosphazene is 1:2.5-3.5. The mass-volume ratio of SiO2@PDA powder to triethylamine is 1:4.5-5.5 g / mL.

[0015] More preferably, the centrifugation speed in step (1) is 8500 rpm and the drying temperature is 100℃.

[0016] More preferably, the concentration of the Tris-HCl buffer in step (2) is 10 mM, and the amount of dopamine hydrochloride added is 0.4 g.

[0017] More preferably, the amount of HCCP added in step (3) is 3g, and the amount of TEA added is 5mL.

[0018] An epoxy resin flame retardant based on SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles is prepared by compositing SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles with epoxy resin to obtain an epoxy resin / SiO2@PDA-HCCP composite material. The preparation method includes the following steps:

[0019] (a) The SiO2@PDA-HCCP prepared by the above method is dispersed in acetone and ultrasonically treated for 0.4-0.6 hours;

[0020] (b) Add the dispersion to epoxy resin preheated at 80-85℃ and stir for 1-2 hours;

[0021] (c) Add 20%-30% of diaminodiphenylmethane (DDM) by weight of epoxy resin, mix well and then inject into the mold;

[0022] (d) Step curing: First cure at 100-110℃ for 1.5-2.5 hours, then cure at 150-160℃ for 1.5-2.5 hours to obtain epoxy resin / SiO2@PDA-HCCP composite material.

[0023] Preferably, the amount of SiO2@PDA-HCCP added is 1-10 wt% of the epoxy resin mass.

[0024] The above method yields a three-dimensional core-shell structured nanoparticle of SiO2@PDA-HCCP, which has a three-dimensional core-shell hierarchical structure consisting of a rigid SiO2 microsphere core, a polydopamine (PDA) intermediate linking layer rich in active sites, and a covalently grafted hexachlorocyclotriphosphazene (HCCP) cross-linked shell. This structure achieves tight covalent bonding of each layer through the strong adhesion and high reactivity of the PDA layer, and significantly enhances the overall stability and mechanical strength with the help of the slightly cross-linked network of the HCCP shell, while providing high-density, flexibly modifiable surface functional sites.

[0025] The above method yields an epoxy resin / SiO2@PDA-HCCP composite material, in which the epoxy resin is a continuous phase, and uniformly dispersed and chemically bonded SiO2@PDA-HCCP core-shell particles are present. These particles consist of a rigid SiO2 core, a PDA connecting layer rich in active groups, and a covalently grafted and lightly cross-linked HCCP functional shell. This unique hierarchical structure not only endows the particles with high stability and high surface reactivity, but also achieves efficient stress transfer in the composite material and significantly reduces the decrease in mechanical strength and modulus of the epoxy resin caused by the addition of silica microspheres.

[0026] The SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles and epoxy resin / SiO2@PDA-HCCP composite materials prepared by this invention can be applied to coatings, adhesives, electronic component encapsulants and civil engineering industries.

[0027] The flame retardant prepared in this invention uses nano-silica (SiO2) as the core, and forms an organic-inorganic hybrid shell (SiO2@PDA-HCCP) by sequentially coating the core surface with polydopamine (PDA) and hexachlorocyclotriphosphazene (HCCP). Specifically, dopamine is oxidatively polymerized under alkaline conditions to form a PDA coating, and the coating is achieved through strong hydrogen bonding between its abundant catechol / amine groups and the surface of SiO2 nanospheres. Subsequently, taking advantage of the high reactivity of PDA, its amine groups undergo a substitution reaction with the active chlorine groups of HCCP, grafting phosphorus- and nitrogen-rich HCCP onto the PDA layer to construct a three-dimensional core-shell structure. The resulting SiO2@PDA-HCCP nanoparticles exhibit good dispersibility in an epoxy resin matrix. Applying this flame retardant to epoxy resin can significantly improve the thermal stability and flame retardant properties of the composite material, for example, by drastically reducing the peak heat release rate (pHRR) by up to 69.8%. Its flame-retardant mechanism is mainly attributed to the synergistic effect of SiO2, PDA, and HCCP, including catalytic char formation, formation of a dense char layer, and gas-phase free radical quenching effects. The flame retardant provided by this invention has the advantages of low addition amount, high flame-retardant efficiency, and minimal negative impact on the mechanical properties of the matrix.

[0028] Compared with existing technologies, the beneficial effects of the present invention are as follows:

[0029] This invention constructs a three-dimensional core-shell structure flame retardant with SiO2 as the core, polydopamine (PDA) as the interface layer, and hexachlorocyclotriphosphazene (HCCP) as the flame-retardant shell, achieving multiple synergistic flame-retardant effects. SiO2 nanospheres enhance the density of the char layer, PDA efficiently captures free radicals and strengthens interfacial compatibility, and HCCP provides phosphorus-nitrogen gas-phase flame retardancy. When the obtained flame retardant is added at 8 wt%, the epoxy resin composite material can achieve a UL-94 rating of V-1 and an LOI value of 30.9%. At the same time, due to the interfacial adhesion effect of PDA, nanoparticle aggregation is inhibited, and the mechanical properties of the composite material are retained at ≥90%. This invention solves the technical bottleneck of traditional flame retardants where high addition amounts (>20 wt%) damage mechanical properties and process adaptability. Attached Figure Description

[0030] Figure 1 These are scanning electron microscope (SEM) images of the SiO2 nanospheres, SiO2@PDA powder, and SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles prepared in Example 1.

[0031] Figure 2 The infrared spectra of the SiO2 nanospheres, SiO2@PDA powder, and SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles prepared in Example 1 are shown.

[0032] Figure 3 The figures show the thermal decomposition curves of SiO2 nanospheres, SiO2@PDA powder, and SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles prepared in Example 1 under nitrogen conditions.

[0033] Figure 4 The images show the XRD patterns of the SiO2 nanospheres, SiO2@PDA powder, and SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles prepared in Example 1.

[0034] Figure 5 These are the LOI and UL-94 figures for EP / 8% SiO2, EP / 8% SiO2@PDA, EP / 8% SiO2@PDA-HCCP, and EP / 6% SiO2@PDA-HCCP in Example 4.

[0035] Figure 6 This is a graph showing the tensile strength and tensile modulus of EP / 8% SiO2, EP / 8% SiO2@PDA, and EP / 8% SiO2@PDA-HCCP in Example 4. Detailed Implementation

[0036] To better understand the present invention, specific embodiments are given below for further explanation. It should be noted that the following embodiments should not be construed as limiting the scope of protection of the present invention, that is, the present invention is not limited to the following embodiments.

[0037] Example 1

[0038] A method for preparing SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles includes the following steps:

[0039] (1) Weigh 9 mL of ammonia water (NH3·H2O), 16.5 mL of deionized water, and 24.5 mL of anhydrous ethanol, and mix them thoroughly to prepare solution A. Separately weigh 4.5 mL of tetraethyl orthosilicate (TEOS) and 25.5 mL of anhydrous ethanol, and mix them to prepare solution B. Quickly pour solution B into solution A, and stir the mixture at 30 °C for 2 hours. After the reaction is complete, centrifuge the suspension at 8500 rpm for 3 minutes. Wash the precipitate three times with anhydrous ethanol, transfer it to an oven, and dry it at 80 °C for 12 hours to obtain white powdered SiO2 nanospheres.

[0040] (2) Take 1.0 g of the SiO2 nanospheres obtained in step (1), add 50 mL of Tris-HCl buffer solution (concentration 10 mM, pH = 8.5), and sonicate for 10 minutes. Add 0.4 g of dopamine hydrochloride and mechanically stir at room temperature (25℃) for 24 hours. After the reaction is complete, centrifuge the mixture at 10000 rpm for 5 minutes, wash the precipitate three times with deionized water, and vacuum dry at 80℃ for 6 hours to obtain black SiO2@PDA powder.

[0041] (3) 1.0 g of SiO2@PDA powder obtained in step (2), 3.0 g of hexachlorocyclotriphosphazene (HCCP), and 5.0 mL of triethylamine (TEA) were added to 50 mL of tetrahydrofuran (THF). Under nitrogen protection, the mixture was stirred in an oil bath at 50 °C for 24 hours. After the reaction was completed, the mixture was centrifuged at 10,000 rpm for 5 minutes. The precipitate was washed three times with THF and dried under vacuum at 60 °C for 12 hours to obtain gray-black SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles.

[0042] Example 2

[0043] (1) Solution A was prepared by mixing 5.5 mL of ammonia water (NH3·H2O), 24 mL of deionized water, and 20.5 mL of anhydrous ethanol; solution B was prepared by mixing 2.8 mL of TEOS and 27.2 mL of anhydrous ethanol. Solution B was quickly added to solution A, and the mixture was stirred at 25 °C for 1 hour. After centrifugation at 8500 rpm for 5 minutes, the solution was washed three times with ethanol and dried at 80 °C for 14 hours to obtain SiO2 nanospheres.

[0044] (2) Disperse 1.0 g of SiO2 nanospheres in 5 mM Tris-HCl buffer (pH = 8.5). Add 0.3 g of dopamine hydrochloride (mass ratio 1:0.3) and stir at 20 °C for 20 hours. Centrifuge at 10000 rpm for 5 minutes and wash with water 3 times to obtain SiO2@PDA.

[0045] (3) Take 1.0 g of SiO2@PDA powder, 2.5 g of HCCP, and 4.5 mL of TEA and add them to 50 mL of THF. Stir and react at 45 °C for 20 hours. After centrifugation, wash three times with THF and dry under vacuum at 60 °C for 12 hours to obtain gray-black SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles.

[0046] Example 3

[0047] (1) Solution A was prepared by mixing 9.5 mL of ammonia water (NH3·H2O), 15 mL of deionized water, and 25.5 mL of anhydrous ethanol; solution B was prepared by mixing 4.8 mL of TEOS with 25.2 mL of anhydrous ethanol. Solution B was quickly added to solution A, and the mixture was stirred at 35 °C for 3 hours. After centrifugation at 9000 rpm for 3 minutes, the solution was washed three times with ethanol and dried at 110 °C for 10 hours to obtain SiO2 nanospheres.

[0048] (2) Disperse 1.0 g of SiO2 nanospheres in 15 mM Tris-HCl buffer. Add 0.5 g of dopamine hydrochloride (mass ratio 1:0.5) and stir at 25 °C for 28 hours. Centrifuge and wash with water to obtain SiO2@PDA.

[0049] (3) Take 1.0 g of SiO2@PDA powder, 3.5 g of HCCP, and 5.5 mL of TEA and add them to 50 mL of THF. Stir and react at 55 °C for 28 hours. After centrifugation, wash three times with THF and dry under vacuum at 60 °C for 12 hours to obtain gray-black SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles.

[0050] Comparative Example 1

[0051] Bisphenol A type epoxy resin (E-44) and epoxy resin curing agent diaminodiphenylmethane (DDM) are mixed in a ratio of 4:1, then degassed for 30 minutes, poured into a preheated mold, cured at 100℃ for 2 hours, cured at 150℃ for 2 hours, and then cooled to demold epoxy resin product A.

[0052] Example 4

[0053] The SiO2 nanospheres, SiO2@PDA powder, and SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles prepared in Example 1 were mixed with bisphenol A type epoxy resin (E-44) and epoxy resin curing agent diaminodiphenylmethane (DDM) in a ratio of 8:80:20. The SiO2 nanospheres, SiO2@PDA powder, and SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles were first ultrasonically dispersed with acetone, then epoxy resin was added and stirred evenly. After degassing for 30 minutes, the mixture was poured into a preheated mold and cured at 100°C for 2 hours and 150°C for 2 hours. After cooling, the mixture could be demolded to obtain EP / 8% SiO2, EP / 8% SiO2@PDA, and EP / 8% SiO2@PDA-HCCP.

[0054] The three-dimensional core-shell structured nanoparticles of SiO2@PDA-HCCP prepared in Example 1 were mixed with bisphenol A type epoxy resin (E-44) and epoxy resin curing agent diaminodiphenylmethane (DDM) in a ratio of 8:75:25. The mixture was poured into a preheated mold and cured at 100°C for 2 hours and 150°C for 2 hours. After cooling, the mixture could be demolded to obtain EP / 6% SiO2@PDA-HCCP.

[0055] Figure 1 Images (a), (b), and (c) in Example 1 are SEM images of the SiO2 nanospheres prepared in step (1), the SiO2@PDA powder prepared in step (2), and the SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles prepared in step (3), respectively. The synthesized SiO2 microspheres have smooth surfaces and regular spherical shapes. After being coated with PDA, the surface of SiO2 becomes rough but still maintains a spherical structure. Figure 1 b) indicates that dopamine has successfully self-polymerized on SiO2 microspheres. After the introduction of HCCP, the surface of the SiO2@PDA-HCCP microspheres becomes denser and more irregular, and cross-linking occurs between adjacent microspheres. Figure 1 c), this should be attributed to the covalent interaction formed between the PDA layer and HCCP on the different microsphere surfaces.

[0056] Figure 2 The infrared spectra of SiO2 nanospheres, SiO2@PDA powder, and SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles prepared in Example 1 show that the asymmetric stretching vibration of Si-O-Si appears at 1105 cm⁻¹. -1 The stretching vibrations of Si-OH and Si-O-Si are located at 953 cm⁻¹. -1 With 800cm -1 Approximately 1490cm -1The broad peak at 953 cm⁻¹ is attributed to the aromatic ring structure of dopamine. Typically, after grafting HCCP onto the PDA shell, a COP bond (located at 953 cm⁻¹) can be formed via a nucleophilic substitution reaction between the P-Cl bond and the hydroxyl group. -1 However, because this absorption peak is similar to 953 cm⁻¹... -1 The Si-OH stretching vibration peaks overlap, making it difficult to distinguish their chemical bond characteristics. The successful grafting of HCCP into the PDA shell can be further confirmed by the characteristic absorption peaks of the P=N and PN bonds in the HCCP structure, which appear at 1186 cm⁻¹, respectively. -1 and 849cm -1 .

[0057] Figure 3 The thermal decomposition curves of SiO2 nanospheres, SiO2@PDA powder, and SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles prepared in Example 1 under nitrogen conditions show that pure SiO2 exhibits excellent thermal stability at high temperatures with almost no mass loss. For SiO2@PDA, the mass loss observed below 140℃ is mainly attributed to the volatilization of adsorbed water. In contrast, the TGA curve of SiO2@PDA-HCCP shows a significantly different decomposition behavior: a significant mass loss occurs at approximately 180℃, which is attributed to the difference in the initial degradation-thermal decomposition characteristics of the HCCP component. This further confirms that HCCP has been successfully integrated into the SiO2@PDA system.

[0058] Figure 4 The XRD patterns of the SiO2 nanospheres, SiO2@PDA powder, and SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles prepared in Example 1 show that the original SiO2 sample exhibits typical broad peaks of amorphous silica. After PDA coating and further modification with HCCP, the XRD peak positions remain unchanged, indicating that the amorphous structure of SiO2 is preserved. However, compared with pure SiO2, the diffraction peaks of SiO2@PDA and SiO2@PDA-HCCP in the 10°-20° range are significantly weakened. This decrease in intensity may be due to the formation of a more disordered surface layer during the modification process, thereby disrupting the original packing arrangement of SiO2. Nevertheless, the material as a whole still maintains an amorphous state.

[0059] Figure 5The graphs for LOI and UL-94 of EP / 8% SiO2, EP / 8% SiO2@PDA, EP / 8% SiO2@PDA-HCCP, and EP / 6% SiO2@PDA-HCCP in Example 4 show that the LOI value of pure EP is only 24.9%, and it received no UL-94 rating. After adding 8% SiO2, the LOI increased to 26.6%, but the UL-94 rating was still not obtained. It is noteworthy that the introduction of PDA and HCCP significantly improved the flame retardancy of the EP composite material, as evidenced by the gradual increase in LOI value. The EP / 8% SiO2@PDA-HCCP composite material exhibited the best performance, with an LOI of 30.9% and a UL-94 rating improved from unrated to V-1.

[0060] Figure 6 The tensile strength and tensile modulus graphs for EP / 8% SiO2, EP / 8% SiO2@PDA, and EP / 8% SiO2@PDA-HCCP in Example 4 show that, compared with pure EP (tensile strength 90.5 MPa, elongation at break 7.08%), the tensile strength (50.45 MPa) and elongation at break (4.07%) of the EP / 8% SiO2 composite are significantly lower, possibly because SiO2 agglomerates in the EP matrix. The tensile strength (85.95 MPa) and elongation at break (6.53%) of the EP / 8% SiO2@PDA composite are significantly higher than those of EP / SiO2. This can be attributed to the excellent adhesion of the PDA coating layer, which improves the compatibility between SiO2@PDA and the EP matrix, thereby enhancing interfacial interactions. In contrast, the tensile strength (80.28 MPa) and elongation at break (5.84%) of the EP / 8%SiO2@PDA-HCCP composite decreased slightly. This may be because the reaction of PDA with HCCP consumes the surface -OH / -NH2 groups, which increases the rigidity of the nanoparticles and weakens their compatibility with the EP matrix.

Claims

1. A method for preparing a SiO2@PDA-HCCP core-shell flame retardant, characterized in that, Includes the following steps: (1) Synthesis of SiO2 nanospheres: Solution A was prepared by mixing ammonia, water and anhydrous ethanol; Solution B was prepared by mixing tetraethyl orthosilicate (TEOS) with anhydrous ethanol; Solution B was quickly added to Solution A, stirred and reacted, centrifuged, washed and dried to obtain SiO2 nanospheres; (2) Preparation of SiO2@PDA: The SiO2 nanospheres obtained in step (1) were dispersed in Tris-HCl buffer solution, dopamine hydrochloride was added, the mixture was stirred at room temperature, and SiO2@PDA powder was obtained by centrifugation. (3) Preparation of SiO2@PDA-HCCP: SiO2@PDA powder, hexachlorocyclotriphosphazene and triethylamine were added to tetrahydrofuran, stirred and reacted, and centrifuged to obtain SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles.

2. The preparation method according to claim 1, characterized in that, In step (1), the temperature of the stirring reaction is 25-35℃ and the reaction time is 1-3 hours; the temperature of the drying is 80-110℃ and the drying time is 10-14 hours.

3. The preparation method according to claim 1, characterized in that, In step (2), the mass ratio of SiO2 nanospheres to dopamine hydrochloride is 1:(0.3-0.5), and the concentration of Tris-HCl buffer solution is 5-15mM.

4. The preparation method according to claim 1, characterized in that, In step (2), the stirring time is 20-28 hours.

5. The preparation method according to claim 1, characterized in that, In step (3), the mass ratio of SiO2@PDA powder to hexachlorocyclotriphosphazene is 1:2.5-3.

5. The mass-volume ratio of SiO2@PDA powder to triethylamine is 1:4.5-5.5 g / mL.

6. The preparation method according to claim 1, characterized in that, In step (3), the temperature of the stirring reaction is 45-55℃ and the reaction time is 20-28 hours.

7. A method for preparing an epoxy resin flame retardant based on SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles, characterized in that, Includes the following steps: (a) The SiO2@PDA-HCCP obtained in claim 1 is dispersed in acetone and subjected to ultrasonic treatment; (b) Add the dispersion to the epoxy resin and stir. (c) Add diaminodiphenylmethane, mix well, and then pour into the mold; (d) Step-curing to obtain epoxy resin / SiO2@PDA-HCCP composite material; The amount of SiO2@PDA-HCCP added is 1-10 wt% of the epoxy resin mass; the curing in step (d) is as follows: first, cure at 100-110℃ for 1.5-2.5 hours, and then cure at 150-160℃ for 1.5-2.5 hours.

8. The SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles obtained by the preparation method according to any one of claims 1-6.

9. An epoxy resin flame retardant based on SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles obtained by the preparation method of claim 7.

10. The application of the SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles as described in claim 8 or the epoxy resin flame retardant based on SiO2@PDA-HCCP three-dimensional core-shell structured nanoparticles as described in claim 9 in coatings, adhesives, and electronic component encapsulants.